(untitled) - Arya, D. P. (Hoboken, N.J., 2007)
During the last twenty years, there have been numerous advances in the understanding of the chemistry, biochemistry, and recognition of aminoglycosides. This has led to the development of novel antibiotics and opened up new therapeutic targets for intervention. This is the first book to provide a complete overview of recent advances in the field and explore their tremendous potential for drug discovery and rational drug design. With chapters written by one or more leading experts in their specialty areas, the book addresses the chemistry, biology, and toxicology of aminoglycosides.
Keywords: Aminoglycosides,Antibiotics,Aminoglycosides,Thuốc kháng sinh; Physiological effect,Hiệu ứng sinh lý